Embryological study of crosses between Vigna unguiculata and V. vexillata - Barone, A.; Ng, N.Q. (1990)
Early embryogenesis up to 8 days after pollination was characterized in V. unguiculata. When crosses were performed between V. unguiculata and wild V. vexillata, seeds were not obtained due to crossability barriers. In most cases pollen tube growth was arrested in the stigmatic tissue. In the 15-20% of ovules which were fertilized, embryo development was normal up to the globular stage, but then (5-8 days after pollination) the embryo began to collapse.